ANALISIS DAN RISIKO METODE FAST TRACK DAN CRASH PROGRAM PADA PROYEK GEDUNG - A'izzatul Khiyana; Titin Sundari; Totok Yulianto; Meriana Wahyu Nugroho; Achmad Imam Agung (LPPM Universitas Negeri Jakarta, 2025)
Project delay is a major issue in execution, often causing cost overruns if not addressed. Acceleration helps meet targets and increase profits. Research on fast track and crash programme methods is extensive, but mainly focuses on case studies rather than risks or work quality. Building X’s construction project faced a 3rd-week delay, extending from 23 weeks (December 2022) to 25 weeks (January 2023). This study aims to determine the most time- and cost-efficient acceleration method using primary (questionnaire) and secondary data (S-curve, unit price analysis, budget plan, and project reports). Applying fast track and crash programme methods along with risk frequency analysis, the study identifies the fast-track method as optimal, reducing project time to 22 weeks with 12% efficiency and Rp. 759,698,484.61 in cost savings. However, a potential risk is concrete cracks due to acceleration. This research complements previous studies by integrating risk analysis and quality assessment in fast-track acceleration.